EDAN MAKNA VERBA LIHAT DALAM BAHASA DAYAK KANAYATN DIALEK AHE - Ayuni Ayuni; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2020)
AbstractThe research of field of meaning of verb see in Dayak Kanayatn Language of ahe dialect is a semantic study conducted at Lingga Village, Sungai Ambawang District of Kubu Raya Regency. Furthermore, this study was aimed to determine the components and the types of meaning in Dayak Kanayatn of Ahe dialects. This research was conducted using a descriptive method in form of qualitative approach. In this study, the techniques used in collecting the data were face to face talking, note-taking technique, and recording technique. Meanwhile, the tools were used like a voice recorder, a list of question, a notebook, and a pen.The results of this study indicated that there are 35 verb lexemes of the verb See in Dayak Kanayatn language. Then, the components of the meaning of the verb See in Dayak Kanayatn dialect of Ahe are divided based on the eyelids, saw with the naked eyes, the target of seeing, the visibility, the duration of seeing, the point of stared at, and the purpose of seeing. Therefore, there 36 lexical meanings were found in the types of meanings and 25 grammatical meanings in the types of meanings.Keywords: The Field Of Meanings, Verb See, Dayak Kanayatn